Determinants of Occupational Safety and Health Performance in Small and Medium Manufacturing Settings - Mohammad Khan, Haji Jamal Khan (2003)
Existing literature reveals a gap in the empirical knowledge in respect of the determinants of OSH performance in SMEs in Malaysian manufacturing settings. In this study, a research model based on the theoretical framework was developed indicating the relationships among several factors that have been argued as important to OSH performance. The concept of OSH performance was operationalised and its relationship with the predictors was hypothesised. The questionnaire was developed based on earlier works by Molenaar et al. (2002) and Burke et al. (2002), and was pre-tested. The research objectives are to identify the determinants of occupational safety and health (OSH) performance and their relationships, and to determine the relationship of two intervening variables on OSH performance. Eighteen hypotheses were developed and tested. Cross-sectional data based on the questionnaire was collected using postal survey method. The study employed simple stratified random selection procedure based on SOCSO database for the process of selecting sampling units for data collection. One hundred and eighteen SMEs in Peninsular Malaysia participated in this study. Statistical analyses used include Pearson-r con-elation, independent T-test, one-way ANOVA, multiple regression, and path analysis. Descriptive statistics were also employed. The results revealed that the independent variables - management commitment? employee’s involvement, safety training, safety incentives were positively related and safety disincentive was negatively related to OSH performance. Therefore, rejecting the null hypotheses of Hl to H7. These variables significantly explained 68.0% (R-square = 0.68) of the variance in OSH performance (F = 50.3 17; Sig. = .OOO). Correlation analysis revealed significant association between OSH performance and each of the seven variables - management commitment (t = 3.059; Sig.= 0.003) employee’s involvement (t = 3.016; Sig. = 0.003). safety training and education (t = 2.665; Sig. = 0.009) safety incentives (t = 1.745: Sig. = 0.084) and safety dis-incentive (t = -1.904; Sig. = 0.059). and were influential factors on OSH performance with standardized beta of 0.322, 0.313, 0.252, 0.158, and -0.164, respectively. The study also reveals that there was no significant difference between the types of industries within the manufacturing sector (F =1.3 11; p = 0.227). and significantly different between small and medium size enterprises (t = -2.8 16; p = 0.006). The study highlighted that there was significant difference in OSH performance between firms having OSH policy (t = 3.490; p = 0.001) and firms without such policy. Similarly, there was significant difference in OSH performance (t = -2.445; p = 0.016) between firms having OSH committee and firms without such committee. The study also highlighted that there was no significant different in OSH performance between firms that have qualified safety personnel (t = -1.385; p = 0.169) and firms without. The study also indicated that there was no significant difference in OSH performance between numbers of years in business (F = 0.145; p = 0.865). The findings further demonstrated that structural equation modelling (SEM) measures (GFI = 0.985; RMR = 0.028; NFI = 0.989: CFI = 0.990 & IFI =0.991) indicating model fit and provided evidence to deem that results were an acceptable representation of the hypothesized relationships of variables. The results indicated that all the five observed exogenous variables (management commitment, employee’s involvement, training and education, safety incentives, and disincentives) significantly explained 41.0 % of variance in safety value and 9.0% variance in behaviour-based safety, and jointly explained 7 1.0% of variance in OSH performance (observed endogenous variables). The result indicated that the direct effects of independent variables were stronger than the indirect effects of intervening variables on OSH performance. The direct effects demonstrated that the independent variables were significantly related to OSH performance. Thus, evidence indicating that null hypotheses (H9 to H18) could not be rejected at 95% confidence level. The study also highlighted that the relationships of independent variables were more significant than the direct relationships of intervening variables. However, of the two indirect relationships, safety value was a more important factor (beta = 0.14) than behaviourbased safety (beta = 0.004). In conclusion, the independent variables (management commitment (beta = 0.242), employee’s involvement (beta = 0.327), safety training and education (beta = 0.203), safety incentives (beta = 0.132) and disincentives (beta = -0.119)) were significant determinants of OSH performance in small and medium firms within manufacturing industry than the intervening variable (safety value and behaviour based safety).